Hubungan stres akademik siswa dengan hasil belajar - Mufadhal Barseli; Riska Ahmad; Ifdil Ifdil (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2018)
This research is based on the  lack of students’ learning outcomes,  which is influenced by the academic stress. The purpose of the study is to describe the academic stress, students’ learning outcomes, and the identification of the relationship between academic stress with students’ learning outcomes. The study showed that the  students’ in general academic stress are in middle category, and generally students’ learning outcomes are in the sufficient category, there is a significant relationship between academic stress with student learning outcomes. The implications of the study are expected to provide counseling teacher guidance and counseling services that are preventive against academic stress and improve student learning outcomes.